BLC and Subordination in Heritage Speakers—Towards a New Research Agenda: Commentary on Hulstijn (2024) - Jeanine Treffers-Daller (Languages)
In his update on Basic Language Cognition (BLC), Hulstijn formulates a number of predictions derived from BLC Theory, and explains how BLC differs from Extended Language Cognition (ELC). BLC is used to refer to an individual’s capacity to process spoken language productively and receptively in everyday life, while ELC is defined as control of the written standard language, as taught in school. In the literature on heritage speakers, so far surprisingly little attention has been paid to the differences between BLC and ELC, despite the relevance of the distinction between oral and written language for our understanding of heritage speakers’ language profiles. In this commentary, I argue that BLC Theory can be used to inform studies of heritage languages, and conversely, how insights from heritage languages can be used to develop BLC Theory further. By way of example, I revisit some of the literature on subordination in Turkish as a heritage language. I also point to issues that need to be clarified and future directions in the study of these phenomena.